Reliability for Generalized Rayleigh of 1 Strength - 4 Stresses - Khaleel, Ahmed Haroon (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
In this paper, the reliability of a one-component model is found where this component is subjected to four stresses with random variables Y1, Y2, Y3, Y4 and this component resists these stresses with its strength with random variable X and it was assumed that these variables follow a generalized Rayleigh distribution. The model's reliability was estimated by three different estimation methods (Percentile method, the Regression method, and the Least Squares method). A Monte Carlo simulation was performed to compare the results obtained from the estimate using two statistical criteria: the mean squares error criterion and the mean absolute percentage error criterion. The comparison showed that the best estimator of the reliability of the model is the favorable Percentile estimator.